1999
DOI: 10.1046/j.1365-2133.1999.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the human homologue ofDrosophila patched(PTCH) in skin tumours: specificity for basal cell carcinoma

Abstract: The human homologue of the Drosophila segment polarity gene patched (PTCH) has been identified as the gene for the naevoid basal cell carcinoma (BCC) syndrome and has also been shown to be mutated in sporadic BCC. In order to elucidate the specificity of the PTCH abnormality in BCC, we examined normal skin and 12 BCC and 24 other types of tumour from Japanese patients for expression of the PTCH transcript by competitive reverse transcription-polymerase chain reaction, as mutational inactivation of PTCH leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Such an antibody is described here. Previous work had demonstrated overexpression of PTCH transcripts in BCNS and sporadic BCCs using quantitative RT‐PCR and in situ hybridization8, 17, 18. Our data now indicate that the pattern of PTCH expression in BCC is similar to the distribution of PTCH transcripts.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Such an antibody is described here. Previous work had demonstrated overexpression of PTCH transcripts in BCNS and sporadic BCCs using quantitative RT‐PCR and in situ hybridization8, 17, 18. Our data now indicate that the pattern of PTCH expression in BCC is similar to the distribution of PTCH transcripts.…”
Section: Discussionsupporting
confidence: 79%
“…Increased levels of PTCH transcripts have been reported in both familial and sporadic BCCs by several groups, using either in situ hybridization or quantitative RT‐PCR16, 17. The pattern of expression observed involves focal high levels of transcripts in both the outer palisading basal cell layer and in tumour epithelial nests, as well as in deep follicular BCCs, in comparison to both superficial BCC and normal covering skin17, 18. However, it is not known whether increased levels of transcription are mirrored by overexpression of the corresponding protein.…”
Section: Introductionmentioning
confidence: 99%
“…The PTC gene 13,41 . Expression studies with in situ hybridization and RT-PCR have shown PTC overexpression in BCCs as compared with normal skin 32,41 . Previous studies have demonstrated that SMO is also overexpressed in BCC, whereas SHH is expressed in only some BCCs 21,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in the differentiation of BCC from trichoepithelioma, both may show increased target gene expression 20,24 , 39 . However, the level of target gene expression may help to differentiate between superficial BCC and actinic keratosis 74 and in assessing whether a hair follicle or BCC is present at an excision margin 75 …”
Section: How Does Molecular Analysis Impact On the Minimum Dataset Fomentioning
confidence: 99%